Clinical Orthopaedics and Related Research® - Leopold, Seth S.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
As of January 1, 2018 Springer will no longer be the publisher of Clinical Orthopaedics and Related Research Subscribers will maintain access to paid for content through SpringerLink Forthcoming issues will be available via Wolters Kluwer.
Keywords: Medicine; Orthopedics; Sports medicine; Surgery; Orthopedics; Surgical Orthopedics; Medicine/Public Health, general; Surgery; Sports Medicine; Conservative Orthopedics